Representing GASPEC with the World Gas Model - Ruud Egging; Franziska Holz; Christian R. von Hirschhausen; Steven A. Gabriel (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
This paper presents results of simulating a more collusive behavior of a group of natural gas producing and exporting countries, sometimes called GASPEC. We use the World Gas Model, a dynamic, strategic representation of world gas production, trade, and consumption between 2005 and 2030. In particular, we simulate a closer cooperation of the GASPEC countries when exporting pipeline gas and liquefied natural gas; we also run a more drastic scenario where GASPEC countries deliberately withhold production. The results shows that compared to a Base Case, a gas cartel would reduce total supplied quantities and induce price increases in gas importing countries up to 22%. There is evidence that the natural gas markets in Europe and North America would be affected more than other parts of the world. Lastly, the vulnerability of gas importers worldwide on gas exporting countries supplies is further illustrated by the results of a sensitivity case in which price levels are up to 87% higher in Europe and North America, but non-GEC countries increase production by a mere 10%.
Keywords: 330; Natural gas; trade; cartel; collusion; World Gas Model; Gaswirtschaft; Kartell; Wirtschaftspolitische Wirkungsanalyse; Erdgas; Preis; Erdgasmarkt; Außenhandelspreis; Welt